An integrated hypothesis on the domestication of Bactris gasipaes - Galluzzi, Gea; Dufour, D.L.; Thomas, Evert; Zonneveld, Maarten van; Escobar Salamanca, Andrés F.; Giraldo Toro, Andrés; Rivera, Andrés; Salazar Duque, Hector; Suárez Baron, Harold; Gallego Sánchez, Gerardo J.; Scheldeman, Xavier; González Mejía, Alonso (Public Library of Science, 2015)
Peach palm (*Bactris gasipaes* Kunth) has had a central place in the livelihoods of people in the Americas since pre-Columbian times, notably for its edible fruits and multi-purpose wood. The botanical taxon includes both domesticated and wild varieties. Domesticated var *gasipaes* is believed to derive from one or more of the three wild types of var. *chichagui* identified today, although the exact dynamics and location of the domestication are still uncertain. Drawing on a combination of molecular and phenotypic diversity data, modeling of past climate suitability and existing literature, we present an integrated hypothesis about peach palm's domestication. We support a single initial domestication event in south western Amazonia, giving rise to var. *chichagui* type 3, the putative incipient domesticate. We argue that subsequent dispersal by humans across western Amazonia, and possibly into Central America allowed for secondary domestication events through hybridization with resident wild populations, and differential human selection pressures, resulting in the diversity of present-day landraces. The high phenotypic diversity in the Ecuadorian and northern Peruvian Amazon suggest that human selection of different traits was particularly intense there. While acknowledging the need for further data collection, we believe that our results contribute new insights and tools to understand domestication and dispersal patterns of this important native staple, as well as to plan for its conservation.